Biotic stress-induced changes in root exudation confer plant stress tolerance by altering rhizospheric microbial community - Sharma, Indrani; Kashyap, Sampurna; Agarwala, Niraj (Frontiers in Plant Science, 2023)
Every organism on the earth maintains some kind of interaction with its neighbours. As plants are sessile, they sense the varied above and below-ground environmental stimuli and decipher these dialogues to the below-ground microbes and neighbouring plants via root exudates as chemical signals resulting in modulation of the rhizospheric microbial community. The composition of root exudates depends upon the host genotype, environmental cues, and interaction of plants with other biotic factors. Cross-talk of plants with biotic agents such as herbivores, microbes, and neighbouring plants can change host plant root exudate composition which may permit either positive or negative interactions spawning a battlefield in the rhizosphere enduring the compatible microbes utilizing the plant carbon sources as their organic nutrients and show robust co-evolutionary changes in changing circumstances. In this review, we have mainly focused on the different biotic factors responsible for the synthesis of alternative root exudate composition leading to modulation of rhizosphere microbiota. Understanding the stress-induced root exudate composition and resulting change in microbial community can help us to devise strategies in engineering plant microbiome to enhance plant adaptive capabilities in a stressful environment.